Use of health belief model to explain the behaviour of following safety measures during the use of household chemical products among adult females in Riyadh - Albadr, Tamador; Alfawzan, Sara; Aljarba, Brooj; Alshehri, Rana; Mahboub, Samira (International Journal of Research in Medical Sciences, 2020)
Background: The hazards and life-threatening conditions resulting from using household chemical products can be avoided or minimized by following certain safety measures. To investigate following safety measures during use of household chemical products (HHCP) among women and to explain that behaviour using the Health belief model (HBM). Methods: This was a cross sectional study. The study was conducted among adult females in Riyadh. The total sample size was 449 by convenience Sampling. this study started in September 2019 till April 2020. the questionnaire included 3 sections which were sociodemographic characteristics, safety measures followed during use of HHCP and the last section assessed the six components of health belief model. Results: Data analysis was done using JMP version 14.2 and the cutoff point of significance was 0.05. 30.3% of the studied sample demonstrated good level of following safety measures. There was no association between the level of following safety measures during the use of HHCP and level of education among studied sample (p value>0.05). The mean of each component of HBM was higher among women with good level of following safety measures than those who follow safety measures poorly. This was significant for perceived susceptibility (1.397 vs 1.269, p=0.03), perceived barriers (8.080 vs 7.038, p=0.0001), self-efficacy (2.889 vs 2.750, p=0.0240) and motivation factors (cues to action) (14.75 vs 13.69, p=0.0001). Conclusions: Health belief model can successfully explain following safety measures behaviour during use of HHCP. Motivation factors has the greatest impact on this behaviour.